Efficiency and Contestability in the Colombian Banking System - Daude, Christian (OECD Publishing, 2015)
Despite progress in the past decade, financial markets in Colombia remain relatively small and shallow. In particular the banking system suffers high intermediation costs, which limit constrains access to finance by households and firms. This paper explores some of the causes behind these intermediation costs. An accounting decomposition of the lending-deposit spread suggests that the levels of contestability and efficiency are low. A more in-depth analysis using stochastic frontier and data envelopment analyses confirm that the efficiency of the Colombian commercial banking system is low compared to other emerging markets and OECD economies with similar levels of development. Furthermore, econometric estimates of market contestability support the hypothesis that contestability in Colombia is subpar. Finally, the paper also explores some of the potential determinants of efficiency and contestability for a sample of the 24 countries over the period 2004 - 2013. This Working Paper relates to the 2014 OECD Economic Survey of Colombia. (www.oecd.org/eco/surveys/economic-survey-colombia.htm)
Keywords: Economics; Colombia